Self-stripping sugarcane - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
Harvesting sugarcane may soon become an easier task. Varieties are being developed in Colombia that drop their leaves just before the cane is ready for harvesting. This avoids the need to burn off the leaves. These self-stripping varieties could...